1929 Neb. Laws 673-74 - (:unkn) unknown (My University, 1929)
Ch. 190, §§ 1-2: Prohibited selling or otherwise disposing of a machine gun. Punishable by fine of $1,000-$10,000. Also Prohibited transporting or possessing a machine gun. Punishable by imprisonment for 1-10 years.
Keywords: MACHINE GUN RESTRICTION